The Beşaret-name sent to Austria with Halil Efendi announcing Osman III’s Accession to the Throne and the Envoy’s Vienna Days According to the Contemporary German Press - Hüseyin Onur Ercan (Tarih Dergisi)
As was customary, the Ottoman Empire would send an official notification of the new sultan’s accession to the throne to the rulers of neighboring and friendly states. These letters that were sent through an envoy belong to the document type known as beşâret-nâme or ilân-nâme [letter heralding (good) news]. The two nâme‑i hümâyûn, preserved in the Austrian State Archive, and announcing Sultan Osman III’s accession were presented on May 14, 1755 to Emperor Franz I and on May 17 to his wife Maria Theresia, Archduchess of Austria by Haci Halil Efendi, as an intermediary alongside a retinue of 54 men.